Measuring the regulatory performance in Malaysia banking industry: Compliance as a lens to determine the regulatory effectiveness and profitability of a financial institution - Thong, Yow Fong (2015)
Development in the region financial market over the past decade have placed great scrutiny on the effectiveness of regulatory and profitability of Malaysia banking industry. This study will explore on how compliance elements work as a lens in determining the regulatory effectiveness of Malaysia based financial institution. And how the given five key determinants such as the compliance awareness and training; internal audit (CA), Unambiguous regulation; (UR) Compliance Culture(CC), Robust system and process (RS); and Non compliance cost and hefty monetary of penalties ( NCC) in formulating the regulatory effectiveness. This study is targeted at in examining the relationships between the extent of compliance with international best practices concerning of operating as well as governance performance. In my research model, return on equity, return on asset, and net interest margin are defined as proxies of profitability, and while capital adequacy are defined as the proxies of regulatory effectiveness. The research collects data from the selected employees both in government and private sector and formulated five hypotheses which are related to the research question. A series of statistical test are performed in order to test if the relationship exists, while other statistical test is to investigate the relationship stable or not. The study performs an ordinal regression analysis of the data from 2008 to 2014. The findings reveal that all the five key determinants have positive significant effect on the regulatory effectiveness. Further test indicate that the financial soundness indicator, such as return on equity (ROE) and return on asset (ROA) are significantly associated with the capital adequacy ratio (CAR). However, in contrast to theory, my reports evidence of a negative relationship between regulatory performance and net interest margin (NIM) of a financial institution. The result generally supported the hypothesized fact that compliance as the catalyst for operational excellence and poor governance malaise. The study recommend that the regulatory authorities both internal and external be involve in the screening and governance monitoring beyond the current compliance practice in both letter and spirit